Research on surface settlement prediction based on the combination prediction model of S-shaped growth curves. Issue 4 (4th July 2018) - Su, Ying; Wang, Xiaoqin; Fu, Yuanyuan; Zheng, Xianjun; You, Gaoshuai
ABSTRACT: After studying the development law of surface settlement induced by excavation of foundation pit and the characteristics of the settlement curve, the paper introduces the idea of combination forecasting based on S-shaped growth curves and establishes the weight combination prediction model, which is applied to the actual project to verify the rationality of the model. Results show that the model cannot only reflect the settlement development process along with time, but also predict the surface settlement accurately. In addition, the combination prediction model is more superior to other single ones, and provides an effective and practical method for surface settlement forecasting.